PEMANFAATAN EKSTRAK DAUN SAMBUNG NYAWA (Gynura Procumbens [Lour].Merr) SEBAGAI ANTIOKSIDAN PADA MINYAK KELAPA MENGGUNAKAN PELARUT METANOL - Mersi Suriani Sinaga, Putri Defriska Siagian, Rika Ariska (Jurnal Teknik Kimia USU, 2017)
Sambung Nyawa leaves (Gynura Procumbens [Lour].Merr) have been used as a traditional medicine. Sambung Nyawa leaves contain flavonoid compounds, its functional as a natural antioxidant. The aim of this study was to analyze the effect of Sambung Nyawa leaves extract addition as an antioxidant and ability to preserve the quality of coconut oil. Firstly, flavonoids were extracted from Sambung Nyawa leaves with combination of raw material to solvent ratio (w/v) and extraction temperature. The extracts which gave the highest total flavonoids contents were mixed into the coconut oil  for 3 days, 6 days, 9 days, 12 days, and 15 days. Total  flavonoids contents of  Sambung Nyawa leaves extracts were analyzed by UV-Vis spectrophotometry. The analyses for coconut oil were the value of acid, iod, and peroxide number. The results showed that the highest total flavonoids contents of  1,32 %  be obtained with raw material to solvent ratio of 1:10 (w/v) and extraction temperature of 55 oC. The lowest acid number of 0.45%, the highest iod number of 7.90 gr I2/100 gr, and the lowest peroxide number of 4.40 mg O2/100 gr be obtained with stored time of 3 days for coconut oil which mixed with the Sambung Nyawa leaves extracts.